Competence of Auditors and Supervisors of The Implementation of Local Government Affairs at The Regional Inspectorate of Tomohon City - Manawan, Christin Carly Merry; Masengi, Evi Elvira; Wawointana, Thelma (Technium Social Sciences Journal, 2023)
This study aims to identify, analyze and describe what factors influence the competence of the Auditor and PPUPD (Supervisor of the Implementation of Local Government Affairs) at the Regional Inspectorate of Tomohon City. In this study, the authors used a qualitative approach that is descriptive in nature, namely explaining the phenomenon in depth through data collection. Based on the results of the study it was found that the competence of Auditors and PPUPD had been implemented. This can be seen from the several indicators that have been discussed, namely, the Auditors and PPUPD who carry out supervisory duties must have sufficient competence. Auditors and PPUPD before carrying out their duties always try to equip themselves with knowledge related to the implementation of the tasks they will carry out. In order to improve the competence of Auditors and PPUPD in carrying out supervisory duties, training is carried out in the office itself concerning the rules relating to the implementation of supervisory assignments. The office training itself also discussed the mechanisms for implementing supervisory assignments. To increase the competence of Auditors and PPUPD in the implementation of supervision, before carrying out supervisory duties, Auditors and PPUPD must prepare an Audit Work Program (PKA), Review Work Program (PKR) as guidelines regarding the design of work procedures systematically, also known as work steps will be implemented to achieve the goal. The Inspectorate, which is the Government's Internal Supervisory Apparatus (APIP) as a Strategic Partner, certainly has many tasks as well as obstacles in the work that are faced within the Internal and External scope. The competence of the Auditor and PPUPD must be maximized and requires a budget that is arranged in the Budget Implementation Document (DPA) of the regional apparatus, in this case, the Inspectorate. Not all Auditors and PPUPD have the opportunity to be involved in training and education regarding the implementation of supervisory duties because the available budget is very limited.